(untitled) (Al-Qamar, 2020)
Sīrah teachers and researchers in Pakistan are facing various problems. This article identifies these challenges and offers solutions. It concludes that there are many issues in this regard such as sectarianism, terrorism, misunderstandings about the status of non-Muslims in Islamic state, Islamophobia, misunderstandings about blasphemy laws, concerns on the religious pluralism in the contemporary word, misunderstandings about Islamic stand on Interfaith Harmony, ignorance regarding the prophetic teachings about minorities’ rights. For remedies this article suggests an exemplary curriculum of Sīrah studies for different educational levels which should be in line with the national requirements of inter-religious harmony.